Maternal exposure to oil spill and children’s mental health: The mediating role of resource loss - Ariane Lisann Rung; Katie M. Sternberger; Evrim Oral; Edward S. Peters (PLoS ONE, 2026)
Objectives To assess the effect of maternal oil spill exposure on children’s mental health and examine whether maternal resource loss mediated this relationship. Methods 445 mother-child pairs from the Women and Their Children’s Health Study in Louisiana (2012–2016) were examined. Maternal oil spill exposure from the 2010 Deepwater Horizon Oil Spill was measured at Wave 1 (2012–2014), while children’s mental health and maternal resource loss were assessed at Wave 2 (2014–2016). Structural equation modeling estimated the direct and indirect effects of maternal oil spill exposure on children’s mental health through maternal resource loss. Results Mothers (mean age 42 years (SD 7.7) and children (mean age 13 years (SD 2.2)) were interviewed. Maternal oil spill exposure was not directly related to children’s mental health (est = −0.08, p = 0.436). However, exposure was associated with increased maternal resource loss (est = 0.45, p < .0001), which was associated with worse children’s mental health (est = 0.27, p < .0001). Maternal oil spill exposure was compatible with an indirect negative effect on children’s mental health (i.e., worse mental health scores) mediated by resource loss (est = 0.12, p < 0.005). Conclusion Findings suggest maternal oil spill exposure indirectly affects children’s mental health through resource loss. Interventions mitigating resource loss are vital for supporting children’s mental well-being after disasters.